ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE TERHADAP PERTENGKARAN RUMAH TANGGA DALAM FILM “PERFECT STRANGERS” - Firmansyah, Herwin; S.S., M.A., Tsuroyya (The Commercium, 2024)
Film is a medium that is often used to represent social reality. The reality of marriages and household disputesis often shown in scenes with the aim of conveying a certain message, as was done in the film "PerfectStrangers". This research examines the representation of domestic quarrels shown in the film "PerfectStrangers" using Charles S. Peirce's semiotics and documentation as a data collection technique, by takingexcerpts from the film to be used as objects of analysis. The research results show that the film "PerfectStrangers" represents household quarrels in three ways, namely 1) the causes of quarrels, in the form ofbetrayal/infidelity and miscommunication, 2) forms of quarrels, in the form of teasing, shouting, unbearableemotions and divorce, 3) solutions to quarrels, in the form of respecting your partner's privacy. Furtherresearch can examine the issue of domestic disputes using other methods